A novel echocardiographic estimate of pulmonary vascular resistance employing the hydraulic analogy to Ohm's law. (October 2022) - Venkateshvaran, Ashwin; Tossavainen, Erik; Borneteg, Charlie; Oktay Tureli, Hande; Vanoli, Davide; Lund, Lars H.; Flachskampf, Frank; Lindqvist, Per
Graphical abstract: Abstract: Background: Assessment of pulmonary vascular resistance (PVR) is critical for accurate diagnosis and optimal pharmacotherapy in pulmonary hypertension. We aimed to test the diagnostic performance of a novel, Doppler-based method to evaluate PVR based on Ohm's law (PVRecho ) using pragmatic estimates of pulmonary capillary wedge pressure (PCWP). Methods and results: Simultaneous right heart catheterization (RHC) and echocardiography was performed in a derivation cohort of 111 patients in sinus rhythm referred for PH evaluation and PVRecho independently validated in 238 patients. PVRecho was calculated using pulmonary artery mean pressure estimates (PAMPecho ) obtained from peak tricuspid gradient employing a fixed right atrial pressure estimate, PCWPecho was estimated as 10 or 20 mmHg using age-related mitral E/A cut-offs and cardiac output from left ventricular outflow. In the derivation cohort, both PAMPecho and PCWPecho estimates demonstrated excellent agreement with catheterization measurements. PVRecho was highly feasible, demonstrated negligible bias and excellent agreement with PVRRHC (Bias = −0.58, SD 2.2 mmHg) and outperformed the Abbas method to identify PVRRHC  > 3WU (AUC = 0.85 vs. 0.70; p = 0.02). In the validation cohort, PVRecho preserved good invasive agreement with negligible bias, displayed strong diagnostic performance (AUC = 0.84) and significant ability to distinguish isolated post-capillary from combined post- and pre-capillary pulmonary hypertension (PH) subgroups (AUC = 0.77). Conclusion: PVRecho based on Ohm's law employing pragmatic estimates of PCWPecho demonstrates excellent agreement with invasive reference standard measurements and strong diagnostic ability to identify elevated PVRRHC . This novel approach may be useful during therapy selection to distinguish PH hemodynamic subgroups.